Backward and forward leaning postures modelled by an fBm framework - Rougier, P.; Burdet, C.; Farenc, I.; Berger, L. (Neuroscience research, 2001)
Body leaning effects on postural control have been assessed by recording the centre of pressure (CP) displacements in healthy subjects under three experimental conditions (REF, BWD and FWD corresponding to upright, backward leaning and forward leaning of the body, respectively). The CP displacements were used to compute the motions of the vertical projections of the centre of gravity (CG v) and those of the difference CP−CG v. A frequential analysis shows that the main effect takes place on CP−CG v motions, suggesting increased muscular activity in these leaning postures. In addition, changes also occur on CG v motions, especially in the antero-posterior (AP) direction. Modelling these motions as fractional Brownian motion (fBm) indicates that leaning the body induces, in the AP direction, a shift in the time interval Δ t at which the corrective process takes over the initial one operating in open-loop. In FWD and BWD conditions, the Δ t is diminished whilst the mean distance covered at this Δ t is increased for both CG v and CP−CG v motions. Moreover, more determinism in the overall upright stance control is observed in the corrective (closed-loop) process involving CG v motions. These facts emphasize the inability for the CP displacements to express properly the overall body sway in upright stance control.